A Model of Cultural Appropriation Through The Indonesian Cultural Festival in Guilin, China - Silvester Rilo Pangestu; Nanang Endrayanto (Journal of Social Research, 2026)
The Indonesian Cultural Festival (FKI) is an annual activity organised by Indonesian students in Guilin, China. This annual event features various forms of Indonesian cultural performance, including dance, music, drama, traditional games, and culinary arts. The festival not only showcases Indonesian art and tradition, but also creates a space for interaction that facilitates cultural exchange. This study examines the model of cultural appropriation through the Indonesian Cultural Festival in Guilin, China. The theoretical framework draws on Richard Schechner's Performance Theory and Homi Bhabha's concept of the "third space," or the space in-between. This study employs a qualitative method with a descriptive approach. Data were collected through questionnaires distributed to international students who had attended or watched the event. The sampling technique used was convenience sampling, selected on the basis of respondent availability. The results of the study show that the festival has a considerable influence in fostering curiosity, understanding, and appreciation for Indonesian culture. Furthermore, this activity also strengthens relationships and interactions among international students, and opens a broader space for cross-cultural communication.